Kajian Pemanfaatan Limbah Kertas Percetakan untuk Pembuatan Bokasi - Irfan Irfan; Ismail Sulaiman; M. Odit Werdana (Jurnal Teknologi dan Industri Pertanian Indonesia, 2020)
Organical material such as animal dung, husk ash, bran, and sawdust is often used  in bocation production. In this study, the paper waste of printing company at Syiah Kuala University was enriched in the raw material of bocation production. This study was aimed to determine the proportion of paper waste that can be added and the duration of fermentation process in order to produce a good bocation. The method used was a factorial Completely Randomized Design (CRD) which consisting of 2 factors. The first factor was the proportion of paper waste (K) with  4 levels: K1 = 15%, K2 = 25%, K3 = 35%, and K4 = 45%. The second factor was the fermentation duration (L) with 3 levels: L1 = 0 day, L2 = 10 days, and L3 = 15 days. Each treatment was repeated twice so that there were 24 experimental units. The analysis included: water content, total microorganisms, temperature, pH, C element, N element, C/N ratio, organoleptic (texture, aroma, color) and plant growth test. The result showed that additional paper waste with a proportion of up to 35% generally has a positive effect on the quality of the location in terms of water content, pH, nitrogen, texture, aroma, color, and plant growth. The longer the fermentation took place (up to 15 days) the better was the quality of the bocation produced, especially regarding C element, N element, C/N ratio, texture, aroma, color and plant growth. There were 3 interactions with the best plant height namely K3L3 (112.5cm), K3L2 (104 cm) and K2L3 (104 cm). The K3L3 bocation (35% paper waste proportion, 15 days fermentation) was better than the other two interactions in term of highest water content, N, and color value, and the lowest C/N ratio.